SUPPLEMENTATION OF NITROGEN SOURCE IN WHEAT STRAW FOR IMPROVING CELLULOLYTIC POTENTIAL OF GANODERMA LUCIDUM. - PRIYA BATRA,; ROBINKA KHAJURIA, (International Journal of Pharma and Bio Sciences, 2014)
Ganoderma lucidum is recognized as a powerful medicinal fungus because of its pharmacological effects and it is cultivated worldwide, using hardwood sawdust as a substrate in synthetic formulation. However, relative abundance of cereal straws such as wheat straw in an agricultural country like India could be exploited for commercial production of this mushroom. Therefore, solid state fermentation of G. lucidum was carried out to study the effect of supplementation of wheat straw as carbon source with different nitrogen sources, viz, Peptone, Ammonium sulphate, Wheat bran and Rice bran on mycelial growth and cellulolytic potential. The comparison of cellulase and hemicellulase activities revealed that supplementation of nitrogen resulted in increased mycelial growth and cellulolytic potential with a highest ß-glucosidase activity of 1200µg/min/ml, Xylanase activity of 600 µg/min/ml and Endo-1,4-ß-D-glucanase activity of 213 µg/min/ml at 20% rice bran concentration. So, it can be inferred that Wheat straw can be optimized to be a good substrate for cellulase production and its utilization by Ganoderma lucidum can be improved considerably with the supplementation of rice bran.